2017
DOI: 10.1002/elan.201700249
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of Metallophthalocyanines Carrying Redox Active Metal Centers and their Electrochemical Pesticide Sensing Application

Abstract: In this study, modified electrodes were constructed with the electropolymerization of metallophthalocyanines (MPcs) carrying redox active metal cations and electropolymerizable substituents. Then these electrodes were tested as selective and sensitive electrochemical pesticide sensors. Incorporation of the redox active Co(II) (CoPc(MOR‐NAF)), Cl–Mn(III) (MnPc(MOR‐NAF)), and Ti(IV)O (TiOPc(MOR‐NAF)) metal cations into Pc cavity increased the redox activity of Pc ring. Moreover, redox active and electropolymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In our previous papers, we have reported various selective pesticide sensors based on MPcs. 4,20 For instance, the electropolymerized film of CoPc(ma) based sensor detected the fenitrothion with good selectivity and sensitivity. 4 In another study, [CoPc(ea)], [Cl-MnPc(ea)], and Ti(IV)O [TiOPc(ea)] based sensors were tested as the pesticide sensors and it was found that GCE/CoPc(ea) electrode detected the fenitrothion pesticide, GCE/MnClPc(ea) electrode detected eserine and GCE/TiOPc(ea) electrode detected parathion with good selectivity and high sensitivity and small LOD values of 8.88 10 −8 , 6.43 10 −7 , 8.64 10 −7 moldm −3 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous papers, we have reported various selective pesticide sensors based on MPcs. 4,20 For instance, the electropolymerized film of CoPc(ma) based sensor detected the fenitrothion with good selectivity and sensitivity. 4 In another study, [CoPc(ea)], [Cl-MnPc(ea)], and Ti(IV)O [TiOPc(ea)] based sensors were tested as the pesticide sensors and it was found that GCE/CoPc(ea) electrode detected the fenitrothion pesticide, GCE/MnClPc(ea) electrode detected eserine and GCE/TiOPc(ea) electrode detected parathion with good selectivity and high sensitivity and small LOD values of 8.88 10 −8 , 6.43 10 −7 , 8.64 10 −7 moldm −3 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…7,[15][16][17][18] Recently we have tested various MPcs as electrocatalysts and electrochemical sensors. 7,[19][20][21][22] It was well reported in these applications that besides the functionality of MPcs, electrode modification techniques significantly influenced the activity of the sensors. MPc films on a substrate could be prepared with different techniques, such as spin coating, physical vapor deposition, molecular beam deposition, Langmuir-Blodgett deposition (LB), electropolymerization, electrodeposition or covalent anchoring.…”
mentioning
confidence: 99%
“…Linear range, sensitivities and LODs obtained from different sensors for Cl2 gas and pesticides: fenitrothion, diazinon and eserine. ( [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], Cl2 is recognised as a toxic gas with an occupational exposure limit of 500 ppb [71]. Exposure to Cl2 gas for an average of six hours can lead to respiratory complications and sensory irritation [72].…”
Section: Gas Sensorsmentioning
confidence: 99%
“…In addition, their unique electronic and chemical properties, physical and optical properties, as well as their chemical flexibility of phthalocyanines allow preparation of variety of related structures and diverse applications ranging from industrial to biological areas [3,4]. Phthalocyanines have been used in different areas such as photodynamic therapy [5,6], nonlinear optical materials [7], electrochemical sensors [8,9], biosensors [10], solar cells [11,12], light-emitting decives [13], liquid crystals [14], electrocatalyts [15], electropolymerization [16,17]. The solubility of unsubstituted phthalocyanines is very low in organic solvents.…”
Section: Introductionmentioning
confidence: 99%